Wearable dual-band Sierpinski fractal PIFA using conductive fabric - Soh, Ping Jack; Vandenbosch, G. A. E.; Ooi, S. L.; Husna, M. R. N. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/